Creative ideation, broad retrieval ability, and processing Speed : A confirmatory study of nested cognitive abilities - Forthmann, Boris; Jendryczko, David; Scharfen, Jana; Kleinkorres, Ruben; Benedek, Mathias; Holling, Heinz (My University, 2019)
Divergent thinking (DT) ability (i.e., the ability to come up with creative ideas) is a complex cognitive construct that has been associated with several specific components of the Cattel-Horn-Carroll (CHC) model. In this study, we employed a nested latent variable approach to examine the specific role of mental speed (Gs) and general retrieval ability (Gr) in DT ability, which was assessed by DT tasks that instructed to be creative and were scored for creative quality. Specifically, Gs was assumed to facilitate both Gr and DT, and Gr was assumed to contribute to DT. Successive latent variable models with orthogonal factors were tested to reflect these nested cognitive basic abilities. The proposed model of nested factors fit the data well: Latent Gs accounted for variation in Gs, Gr, and DT creative quality scores, latent Gr predicted performance in Gr and DT scores beyond Gs, and latent DT explained variation in DT scores beyond Gs and Gr. In addition, we related the resulting orthogonal latent variables to the external criteria of school grades to illustrate the explanatory power of the modeling approach. This study provides evidence that divergent thinking performance relies on mental speed and retrieval ability, as well as cognitive abilities unique to divergent thinking. We discuss consequences for the understanding of divergent thinking ability in the context of the CHC model.
Keywords: Divergent thinking, Broad retrieval ability, Processing speed, Structural equation modeling; 150